Orphée - Gluck, Christoph Willibald 1714-1787; Moline, Pierre Louis c. 1740-1821; Calzabigi, Ranieri de' 1714-1795 (Braunschweig Henry Litolff's Verlag, 1900)
Partition chant et piano
First performed in Vienna at the Burgtheater on 5 October 1762, in Italian, to a libretto by Ranieri de' Calzabig (Orfeo ed Euridice, Wq.30), and in Paris at the Opéra on 2 August 1774, in French, to a libretto by Pierre Louis Moline after Calzabigi.
Ex libris Bibl. L'Abbé Verhelst (manuscript)
Ex libris A. Neriner (manuscript)
Keywords: 18th Century (1701-1800); 19th Century (1801-1900); Opera